Landscapes in transition: an analysis of sustainable policy initiatives and emerging corporate commitments in the palm oil industry - Padfield, R.; Drew, S.; Syayuti, K.; Page, S.; Evers, S.; Campos-Arceiz, A.; Kangayatkarasu, N.; Sayok, A.; Hansen, S.; Schouten, G.; Maulidia, M.; Papargyropoulou, E.; et al. (Routledge, 2016)
The recent Southeast Asian haze crisis has generated intense public scrutiny over the rate, methods and types of landscape change in the tropics. Debate has centred on the environmental impacts of large-scale agricultural expansion, particularly the associated loss of high carbon stock forest and forests of high conservation value. Focusing on palm oil—a versatile food crop and source of bioenergy—this paper analyses national, international and corporate policy initiatives in order to clarify the current and future direction of oil palm expansion in Malaysia and Indonesia. The policies of ‘zero burn’, ‘no deforestation’ and ‘no planting on peatlands’ are given particular emphasis in the paper. The landscape implications of corporate commitments are analysed to determine the amount of land, land types and geographies that could be affected in the future. The paper concludes by identifying key questions related to the further study of sustainable land use policy and practice.